Asymmetries in mother-infant behaviour in Barbary macaques (Macaca sylvanus) - Regaiolli, Barbara (PeerJ, 2018)
Asymmetries in the maternal behaviour and anatomy might play an important role in the development of primate manual lateralization. In particular, early life asymmetries in mother’s and infant’s behaviour have been suggested to be associated with the development of the hand preference of the offspring. The aim of this study was to investigate the presence of behavioural asymmetries in different behavioural categories of mother-infant dyads of zoo-living Barbary macaques (Macaca sylvanus). The study subjects were 14 Barbary macaques involved in seven mother-infant dyads housed in Parco Natura Viva, Italy. For the mothers, bouts of hand preference for maternal cradling and infant retrieval were collected. For the infants, we focused on nipple preference and hand preference for clinging on mother ventrum. Moreover, we collected bouts of hand preference for food reaching in both groups. No significant group-level bias was found for any of the behavioural categories in either mothers or infants. However, at the individual level, six out of seven mothers showed a significant cradling bias, three toward the right hand and three toward the left hand. Moreover, all infants showed a significant nipple preference, six toward the mother’s right nipple, one toward the left nipple. Furthermore, a significant correlation was found between the infant nipple preference and their hand preference for food reaching, suggesting that maternal environment rather than behaviour might affect the development of hand preference in Old World monkeys. Our findings seem partially to add to previous literature on perceptual lateralization in different species of non-primate mammals, reporting a lateral bias in mother-infant interactions. Given the incongruences between our study and previous research in great apes and humans, our results seem to suggest possible phylogenetic differences in the lateralization of mothers and infants within the Primates order.